Localization of person under surveillance using GPS mobile apps - Azemi, Saidatul Norlyana; Iffah Azhar, Nur Hafizah; Amir, Amiza; Che Beson, Rashidi; Kamalrudin, Massila (2023)
Relatively more smartphones developed nowadays come with GPS location software. GPS information is fetched from the satellites and can be retrieved from Bluetooth, wi-fi, cell-id, and a combination of those tools. GPS-based mobile apps have the features of fetching the location of a device using geo-coordinates and some measurement which is an added value in developing various software. Due to the pandemic disease of Covid-19, the world is now aiming for global digitalization. Countries such as Singapore, Chine, and even Malaysia developed applications that can help the citizen in obeying the SOP and receiving current and reliable information regarding the Covid-19 issue. Thus, a real-time monitoring application for PUS s beneficial to break the chain and contain the disease. This research has been done to develop a localization application for Person Under Surveillance using GPS mobile apps. The application implemented the Firebase Authentication in the sign-up and sign-in process and is developed using Android Studio IDE 4.1 integrated with cloud-hosted database Firebase Realtime Database. Android version 6.0 is used which is API level 23. Application is developed to have the functionalities of user registration, fetching coordinates, setting a boundary, and in-app alert. The application was installed and tested on the Pixel 3 API 23 emulator.